Intended and perceived images of a retail store interior - Balingit, Rose Anne M. (UP College of Home Economics, 2012)
Retail design is utilized to create an image for a brand by enhancing the interior of the retail store. The image in relation to the store owner and their designer is defined as the intended image, while the projected appeal to customers conveys the perceived image. Using both the qualitative and quantitative approach of gathering data, the intended image was derived from content analysis of published and online articles of the brand, while the perceived image was drawn from the frequency distribution of the survey questionnaire. The design narrative theory was utilized to organize the intended and perceived image depicted. A total of fifty (50) respondents, who were customers of a particular branch of the retail store, were selected through non-probability sampling. Key findings of the study showed the similarities between the highest, meaning (32.5 perceived frequency, 12 intended frequency), and lowest ranked, order (16.3 perceived frequency, 0 intended frequency), criteria based on perceived and intended image, which were consistent between the two communicated images. The results presented significant difference in the design criteria on the third highest in rank due to motivation. As to the most effective design element, wall finishes with 94% showed to be most familiar and memorable, and the demographic factor highly influencing recall was age with 90.5%. In conclusion, retail design communicates an image effectively by enabling the store owner and its designer to present an image using design elements that was perceived by its customers. This study proposes to incorporate the criteria of the design narrative theory to enrich human experience within space, in order to relate and educate its target market.